A DedA Family Membrane Protein in Indium Extrusion in Rhodanobacter sp. B2A1Ga4 - Caldeira, Joana B.; Chung, Ana Paula; Piedade, Ana Paula; Morais, Paula V.; Branco, Rita (Frontiers in Microbiology, 2021)
Indium (In) is a critical metal widely used in electronic equipment’s and the supply of this precious metal is a major challenge for sustainable development. The use of microorganisms for the recovery of this critical high-tech element has been considered an excellent eco-friendly strategy. The Rhodanobacter sp. B2A1Ga4 strain, highly resistant to In, was studied in order to disclose the bacterial mechanisms closely linked to the ability to cope with this metal. The mutation of the gene encoding for a DedA protein homolog, YqaA, affected drastically the In resistance and the cellular metabolic activity of strain Rhodanobacter sp. B2A1Ga4 in presence of this metal. This indicates that this protein plays an important role in its In resistance phenotype. The negative impact of In might be related to the high accumulation of the metal into the mutant cells that showing In concentration up to approximately 4- fold higher than the native strain. Additionally, the expression of the yqaA gene in this mutant reverted the bacterial phenotype with a significant decrease of In accumulation levels into the cells and an increase of In resistance. Membrane potential measurements showed similar values for native and mutant cells, suggesting that there was no loss of proton-motive force in the mutant cells. The results from this study suggest a potential role of this DedA family protein as a membrane transporter involved in the In efflux process. The mutant strain also has the potential to be used as a biotool in bioaccumulation strategies, for the recovery of In in biomining activities.